Case Report: Area of Focus of Myocardial Infarction With Non-obstructive Coronary Arteries in Eosinophilic Granulomatosis With Polyangiitis - Cui, Xiaoxian; Peng, Yang; Liu, Jun; Dong, Yugang; Wu, Zexuan; Chen, Yili (Frontiers in Cardiovascular Medicine, 2021)
Eosinophilic granulomatosis with polyangitis (EGPA) manisfested as myocardial infarction with non-obstructed coronary arteries (MINOCA) is rarely reported. We report a 43-year-old male patient without any cardiovascular risk factors presenting with acute chest pain. Electrocardiogram was suggestive of acute anterior and inferior myocardial infarction. MINOCA was confirmed based on significant elevated cardiac troponin and normal coronary arteries. Cardiac magnetic resonance (CMR) imaging revealed extended late gadolinium enhancement (LGE). Further diagnosis of EGPA was based on clinical manifestations and auxiliary examination. Subsequent immunosuppressive therapy led to regression of symptoms and significant resolution of LGE on CMR. Our case highlights that EGPA can be a rare cause of MINOCA. CMR is useful for differentiation diagnosis and evaluation of cardiac involvement.